2016
DOI: 10.1016/j.foodchem.2015.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of arsenic bioaccessibility in raw and cooked edible mushrooms by a PBET method

Abstract: The present study reports arsenic analysis in Lentinula edodes, Agaricus bisporus and Pleurotus ostreatus before and after being cooked. Furthermore, arsenic in raw and cooked mushroom was determined in the gastric and gastrointestinal bioaccessible fractions obtained after simulating human digestion by means of an in vitro physiologically based extraction test (PBET). Several certified reference materials (SRM 1568a, SRM 1570a, CRM 7503-a, BC211 and IPE-120) were analysed to evaluate the proposed methods. Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 33 publications
2
13
0
1
Order By: Relevance
“…Bioaccessibility in pakchoi varied from 16.1% to 59.03%, and 20.53% to 82.46% for gastric and gastrointestinal fractions, respectively. The values of As bioaccessibility in pakchoi obtained in the present research were in line with the previous reports for rice [ 26 , 27 ], mushroom [ 28 ] and seaweed [ 29 ]. Thus, a high variability in As bioavailability was observed depending on the different types of food studied.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Bioaccessibility in pakchoi varied from 16.1% to 59.03%, and 20.53% to 82.46% for gastric and gastrointestinal fractions, respectively. The values of As bioaccessibility in pakchoi obtained in the present research were in line with the previous reports for rice [ 26 , 27 ], mushroom [ 28 ] and seaweed [ 29 ]. Thus, a high variability in As bioavailability was observed depending on the different types of food studied.…”
Section: Resultssupporting
confidence: 93%
“…In vitro digestion methods, based on the human gastrointestinal system, have been proposed and successfully used to study the bioaccessibility and risk assessment of contaminants (e.g., metals) from various soils and foods [ 20 , 21 , 22 , 23 , 24 , 25 ]. With regard to heavy metals in food, a limited number of Cd and As bioaccessibility studies have been reported, so far, mostly concerning rice [ 22 , 26 , 27 ], mushrooms [ 28 ], edible seaweeds [ 29 , 30 ], and seafood [ 31 ]. Only few studies have investigated the bioaccessibility of Cd and As in vegetables [ 23 , 32 , 33 ], and as previously mentioned, most of these studies only focused on the bioaccessibility of single toxic metals.…”
Section: Introductionmentioning
confidence: 99%
“…However, some other metal elements are considered to be harmful, such as arsenic, cadmium and lead (Liu et al, 2015). It is well documented that the fruiting bodies of mushrooms have the ability to bioaccumulate metal ions, and the accumulation of heavy metals in macrofungi has been proven to be affected by environmental and fungal factors (Garcia et al, 1998, Llorente-Mirandes et al, 2016). Heavy metal concentrations and those of several trace minerals in mushroom are considerably higher than those in agricultural crop plants, vegetables and fruit (Dursun et al, 2006).…”
Section: Effects Of Intrinsic Factorsmentioning
confidence: 99%
“…Experimental data on the differences on contents in arsenic concentration in the dry biomass of mushrooms versus the fresh biomass are important to encourage off-season supply and consumption of dry mushrooms in meals. [56] Llorente-Mirandes, Llorens-Muñoz, Funes-Collado, Sahuquillo and López-Sánchez [57] examined the fate of total arsenic when cooking (boiling and gridding) the cultivated mushrooms species such as A. bisporus, P. ostreatus and L. edodes. Boiling of A. bisporus, P. ostreatus and L. edodes with double distilled water for 10 minutes (once the mushrooms had been cooked, the cooking water was removed.)…”
Section: Nutritional Value and Health Benefits Of Mushroom Powdermentioning
confidence: 99%